Structured literature review of transport networks and Supply Chain Resilience - Johannes Gast; Evelina Kirkach; Dmitry Ivanov (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: The literature on Supply Chain Resilience faces a steep and significant interest in recent years owing to the pandemic and disruptions in global trade. As the literature amplifies due, this paper aims to provide transparency about the intersection of Supply Chain Resilience and transport networks. Existing literature reviews do not consider this aspect. Methodology: This paper conducts a Systematic Literature Review using the keywords "Supply Chain Resilience" combined with "Transport/Infrastructure networks" to identify the relationship between transport networks and Supply Chain Resilience. The method, as a result, identifies about 251 articles from 2004 to 2022, of which 36 relevant papers are included. Findings: Excluded overview papers address Supply Chain Resilience and transport independently. As a result of the full-text screening, a shift to quantitative methods can be observed. Network theory and mathematical programming models stick out. However, a list of specific research gaps for future research proposed in the literature remains. In particular, a dedicated transport network like highways is seldomly considered. Originality: This research improves the understanding of the relationship between Supply Chain Resilience and transport networks with the interrelation of transport and supply chain disruptions.
urn:nbn:de:gbv:830-882.0200920; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Supply Chain Risk Management; Security Management